Rethinking Nature in Japan (Edizioni Ca’ Foscari – Venice University Press, 2026)
This volume brings together the papers of the International Symposium Rethinking Nature in Japan: from Tradition to Modernity held at Ca’ Foscari University of Venice in 2014 with the support of the Japan Foundation. The Symposium, focused on Fine Arts, Religion and Thought, Literature, Theatre and Cinema was the perfect occasion to rethink about the relationship between Man and Nature in our World and particularly in Japan after the accident at Fukushima nuclear plant in March 2011.